Ocular surface microbiome in meibomian gland dysfunction. (7th September 2016) - Watters, Grant A; Turnbull, Philip R; Swift, Simon; Petty, Alex; Craig, Jennifer P
Abstract: Background: To investigate the ocular microbiome in meibomian gland dysfunction in Auckland, New Zealand. Design: Prospective, cross‐sectional, observational, university‐based study. Participants: Participants resident in New Zealand for ≥2 years ( n = 157) were classified as normal ( n = 66), mild ( n = 41) or moderate‐to‐severe meibomian gland dysfunction ( n = 50). Contact lens wear and anterior blepharitis status were recorded, as well as symptoms and clinical features. Methods: Bacteria collected from lid margin swabs, before and after gland expression, were isolated and identified by conventional microbiological culture techniques. Aerobic isolates were identified in all 157 participants, and both aerobic and anaerobic bacteria isolated in a subset of 87 subjects. Main Outcome Measures: Bacterial incidence according to meibomian gland dysfunction status Results: Symptoms, bulbar hyperaemia, conjunctival staining, lipid layer grade and tear film stability, but not corneal staining, showed moderate association with meibomian gland dysfunction severity. Participants with and without meibomian gland dysfunction showed a similar microbiome, unaffected by gland expression. Anterior blepharitis, a common co‐morbidity, was not an independent predictor of the microbiome. Sterile cultures were more common in contact lens wearers than non‐wearers. The incidence of Staphylococcus aureus was higher than anticipated across all severity groups, and that of coagulase‐negative Staphylococcus, Corynebacterium and streptococci was lower. Conclusions: Modest differences in relative proportions of bacteria compared with other studies support climatic variations in the ocular surface microbiome. Similarity in microbiome profile, irrespective of meibomian gland dysfunction severity, anterior blepharitis presence or contact lens wear, suggests potential for commonality in treatment.